2007
DOI: 10.1097/01.pcc.0000269378.76179.a0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous venovenous hemofiltration with or without extracorporeal membrane oxygenation in children*

Abstract: Performing CVVH in a heterogeneous population with large age and weight ranges poses significant clinical and technical challenges. The low frequency of CVVH use, as well as the use of other extracorporeal therapies, also raises problems with maintaining nursing skills. Objective clinical and biochemical markers for commencing CVVH alone or in combination with ECMO remain to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Each of these modalities has advantages and disadvantages in critically ill patients who have been reviewed elsewhere [6][7][8][9]. Reported experience with the use of RRT on ECMO consists primarily of single-center reports with a limited number of patients [10][11][12][13]. These studies show conflicting results, with some studies demonstrating improved outcomes, while others describe worsening outcomes with the use of RRT [10][11][12][13].…”
Section: Introductionmentioning
confidence: 94%
“…Each of these modalities has advantages and disadvantages in critically ill patients who have been reviewed elsewhere [6][7][8][9]. Reported experience with the use of RRT on ECMO consists primarily of single-center reports with a limited number of patients [10][11][12][13]. These studies show conflicting results, with some studies demonstrating improved outcomes, while others describe worsening outcomes with the use of RRT [10][11][12][13].…”
Section: Introductionmentioning
confidence: 94%
“…Pediatric CRRT, as well as neonatal CRRT with ECMO, have been limited by case reports, small sample size, and single-center studies, making generalization and standardization of practice difficult across pediatric patients and centers (17,18). Additional reviews of institutional experiences with CRRT and ECMO described the technical challenges and complications associated with continuous venovenous hemofiltration (CVVH) and ECMO using objective clinical and/or biochemical markers (9,16). Recently, Paden et al (19), suggested that the combination of CVVH and ECMO does not contribute to development of chronic renal failure but is associated with higher mortality risk than ECMO alone, probably because of the preexisting renal failure rather than the introduction of CVVH.…”
Section: Discussionmentioning
confidence: 99%
“…CRRT operates via several pathways of inflammatory mediator elimination, to include adsorption, diffusion, and convection (12)(13)(14). Although CRRT has been reported to demonstrate efficacy in the removal of IL-6 in adults with septic shock (15), its use in neonatal and pediatric ECMO populations was initially reported in the setting of concurrent acute renal failure (9,16), Recently, some have suggested expanding the role of CRRT into non-renal settings, such as ECMO, CPB, and septic shock, for its "blood cleansing" abilities (1,12).…”
mentioning
confidence: 99%
“…Certain groups of newborns are recognized as being at increased risk for acute kidney injury. These include the following: infants with perinatal hypoxia [1,36,44,45]; premature and very low birth weight (VLBW) infants [8,47]; infants with congenital heart disease, especially those requiring cardiopulmonary bypass [19,48,63,76]; infants requiring extracorporeal membrane oxygenation (ECMO) [6,10,21,56,71,75,83]; and infants with sepsis Mathur [55]. These infants warrant close monitoring of kidney function with frequent measurement of SCr, close monitoring of intake/output, and attention to modifiable risk factors such as nephrotoxic medications (see Table 16.5).…”
Section: Who Is At Risk?mentioning
confidence: 99%